Analisis Beban Kerja pada Operator Bagian Produksi dengan Menggunakan Metode NASA-TLX (Task Load Index) di PT. Ujong Neubok Dalam - Reji Jaya Putra; Gaustama Putra (Universitas Teuku Umar, 2021)
Operator workload in a company can be grouped into low or high workloads. Operators feel the workload is low if each activity is carried out easily and safely so that it does not exceed the operator's capabilities. Meanwhile, a heavy workload is felt when the work exceeds the operator's ability limit which can cause fatigue and work accidents. PT Ujong Neubok Dalam is a company that produces Crude Palm Oil (CPO) and kernels. In the production section, there are workstations such as loading rump, sterilization, digester and press, clarification, and others. The production target is 270 tons/day of Fresh Fruit Bunches (FFB) which are produced into CPO. The demand for production targets resulted in complaints and discomfort felt by the production department operator. The purpose of this study was to analyze the workload and workload indicators of production operators using the NASA-TLX method. From the calculation results of 17 operators, the mental workload that is classified as high is felt by 7 operators with an average Weighted Workload (WWL) of 81-89, while 10 operators are classified as high mental workloads with a WWL value of 78-67. Of the 6 NASA-TLX indicators, 3 indicators have the highest mental workload values, namely physical needs (KF), effort (U), and work performance (PK) with details of the average value of 248 - 260.